Evaluating China's natural gas supply security based on ecological network analysis. (15th December 2016) - Shaikh, Faheemullah; Ji, Qiang; Fan, Ying
Abstract: Growing role of natural gas as an effective policy choice has kindled the discussions surrounding the security of its supplies in the policy circles of the Chinese government. This study tries to evaluate China's natural gas supply security and employs a system-oriented modelling approach namely, Ecological Network Analysis (ENA) to integrate all the critical compartments of China's natural gas supply system. Several ENA indicators are constructed, which disclose that domestic natural gas production contributes significantly to China's natural gas supply system in comparison with all the external natural gas suppliers. In addition, the variations in a system stability indicator suggest that diversification of external natural gas suppliers has a positive influence on China's natural gas supply security. Furthermore, the results revealed that China's natural gas supply security policy is orchestrated on following features 1) to increase the investment in the upstream natural gas production sector to boost its domestic production in order to reduce its import requirements and 2) to diversify the external natural gas supplies by sources and routes to reduce the level of the economic and supply disruption related risks. Highlights: Natural gas has become one of the policy choices to reduce GHG emission in China. China's natural gas dependency on its external suppliers is rising very fast. External natural gas supply issues are heightened in the recent years. ENA has been introduced to evaluate the stability of natural gas supply in China. The stability of natural gas supply in China has generally increased since 2007.